Occupational Safety and Health (OSH) in Construction Projects in Ternate City - Endah Harisun; Hery Purnomo; Suhartini Suhartini (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
The importance of occupational safety and health (OHS) in the construction industry, especially in the construction project of the operating room at Dr.H. Chasan Boesoirie Ternate Hospital. This study used a questionnaire method and direct observation of respondents involved in the project. The results showed that the project had met occupational standards safety, but there was a need for improvement in the availability of flammable materials and evacuation routes. The company provides adequate PPE and health facilities. Prioritizing OHS in the project can avoid losses and prevent accidents, thus providing long-term benefits.